Diversity Dimensions in Mathematics and Language Learning Perspectives on Culture, Education and Multilingualism - Fritz, Annemarie; Gürsoy, Erkan; Herzog, Moritz (DaZ-Forschung [DaZ-For], 2021)
Extensive research is available on language acquisition and the acquisition of mathematical skills in early childhood. But more recently, research has turned to the question of the influence of specific language aspects on acquisition of mathematical skills. This anthology combines current findings and theories from various disciplines such as (neuro-)psychology, linguistics, didactics and anthropology.